HETEROGENEITY IN HEAVY METAL CONCENTRATIONS IN THE SOIL OF A FIRING RANGE AREA AT KESARIANI, ATHENS, GREECE - Argyraki, A.; Petrakaki, N. (Bulletin of the Geological Society of Greece, 2010)
Heterogeneity in metal concentrations is a typical characteristic of contaminated sampling targets, with consequences in the estimation of measurement Nuncertainty and the spatial delineation of contamination. Heterogeneity of Ncontamination is site specific and is linked to the type and origin of the Ncontaminants. In this paper we present a case study on a completed firing range, at Skopeftirio Park in Kesariani, Athens, Greece. The study focused on two heavy metals in the soil with contrasting properties. Lead, an element with high concentrations due to the previous land use of the park and Cr, an Nelement with concentrations close to the natural background at this site. Forty nine top soils samples (0-10cm) were collected from an area of 0.7 km2 by using a 40m x 40m grid. Duplicate samples were collected from 8 randomly selected sampling sites, 5 m away from the original sampling location and were analyzed in duplicate for the estimation of measurement uncertainly. Elemental concentrations were measured by AAS after an aqua- regia acid attack. Robust analysis of variance applied on duplicate measurements separated the total variability of the results into three components, representing the analytical, sampling and geochemical variances for the two elements in soil. It was shown that the combined sampling and analytical variance for the Pb has a high proportion in the total (53.5%) reflecting the extreme small-scale spatial variation of Pb contamination. For Cr, the proportion is lower (17%) indicating a more homogeneous distribution of elemental concentrations.